(3GdHdZI aj JaSjQ GdbQBf GdcQjes - (3GdYHGS eMeO Hf eMeO Hf CMeO GdMce GdWhSjs
(3ChdgG (B:s
(3JaSjQ ShQI GdReQ s
(3BNQgG (B:s
(3BNQg eHJhQ , jfJgi CKfGA JaSjQ ShQI Gdajd s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG ebGHdGJs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs